Studies of the electrochemical behavior of moniliformin mycotoxin and its sensitive determination at pretreated glassy carbon electrodes in a non-aqueous medium - Diaz Toro, Paulo Cesar (2015)
The electrochemical oxidation of moniliformin (MON) mycotoxin in acetonitrile (ACN) + 0.1 mol dm−3 (C4H9)4NPF6 at electrochemically pretreated glassy carbon electrodes (EPGCE) and fiber disk carbon ultramicroelectrodes (FCUME) is studied for the first time. Electrochemical techniques used were cyclic (CV), convolution and square wave (SWV) voltammetries as well as controlled potential electrolysis. Experimental results allowed inferring a complex electro-oxidation mechanism with adsorption of reactant and homogeneous chemical steps coupled to the electron transfer reaction. The UV–Vis spectroscopy was used as a non-electrochemical technique in order to follow the disappearance/appearance of the reactant/reaction product/s during controlled potential electrolysis. The most probable electro-oxidation mechanism proposed on the base of digital simulation results of cyclic voltammograms is one of the CEC type. Thermodynamic and kinetics parameters were calculated from the fitting of experimental cyclic voltammograms, while the diffusion parameter was calculated from convoluted cyclic voltammograms. We propose that reaction products obtained are produced through the decomposition of the MON radical generated from the electrochemical oxidation of MON anion. On the other hand, the MON quantitative determination was performed using adsorptive SWV at EPGCE. An extremely low detection limit of 1 × 10−11 mol dm−3 (1.2 ppt) for a signal to noise ratio of 3:1 was calculated.